LINC00467 Promotes Tumor Progression via Regulation of the NF-kb Signal Axis in Bladder Cancer - Xiao, Jiawei; Gong, Lian; Xiao, Mengqing; He, Dong; Xiang, Liang; Wang, Zhanwang; Cheng, Yaxin; Deng, Liping; Cao, Ke (Frontiers in Oncology, 2021)
Absctrat Purpose: Long non-coding RNAs plays an important role in the occurrence and development of bladder cancer, whereas their molecular mechanisms of function remain largely unknown. In this study, we found that LINC00467 is significantly highly expressed in bladder cancer through bioinformatic analysis. The present study aims to explore the role of LINC00467 in bladder cancer and its possible molecular mechanism. Methods: The expression of LINC00467 was obtained from the GEO (GSE31189), TCGA database and qRT-PCR respectively. The role of LINC00467 in bladder cancer was assessed both in vitro and in vivo. RIP, RNA pulldown and COIP are used to demonstrate the potential mechanism of LINC00467 in regulating the progression of bladder cancer. Results: Through the analysis of GEO (GSE133624) and TCGA database, it is found that LINC00467 is highly expressed in bladder cancer tissues, and the expression of LINC00467 is significantly negatively correlated with patient prognosis. Cell and animal experiments suggest that LINC00467 can promote the proliferation, invasion and metastasis of bladder cancer. On the one hand, LINC00467 can directly bind to p65 mRNA to stabilize its expression. On the other hand, LINC00467 can directly bind to p65 protein to promote the translocation of p65 into the nucleus, activating the NF-kb signaling pathway, which promotes the progression of bladder cancer. Conclusions: LINC00467 is highly expressed in bladder cancer and can promote the progression of bladder cancer by regulating the NF-kb signaling pathway. Therefore, targeting LINC00467 is very likely to provide a new strategy for the treatment of bladder cancer and improve the prognosis of patients.